Anticoagulation in pulmonary TB induced deep vein thrombosis is it always warranted: a case report - Lodaria, Binal Nitin; Muley, Prasad; Sheth, Dhrumika (International Journal of Research in Medical Sciences, 2020)
India is a densely populated developing country and accounts for one quarter of the total tuberculosis cases reported worldwide. Deep vein thrombosis (DVT) has been associated with 1.5-3.4% cases of tuberculosis. A 14 year female presented with complaints of cough with progressive breathlessness (NYHA Grade III) since 15 days along with easy fatiguability and fever for 3 days. The patient was started on Anti-Tubercular Treatment (ATT) as per RNTCP guidelines after thorough investigations. One week after the patient was started on ATT, the patient developed edema of the right lower limb accompanied by pain. Color doppler was suggestive of thrombosis in the superficial and deep veins. Early immobilization and physiotherapy was started immediately. Over a period of 10 days, the swelling gradually decreased, and pain subsided. Tuberculosis is an independent risk factor for the development of venous thromboembolism irrespective of the presence of other risk factors. Emphasis is thus laid on high index of suspicion and early diagnosis to control and prevent further complications like pulmonary embolism. We can propose that in patients diagnosed with pulmonary tuberculosis, early immobilization and physiotherapy can prevent the development of DVT.